Jambi City under the Dutch Colonial Era, 1906-1942 - Diyah Ayu Putri Maharani; Andre Mustofa Meihan (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This study examines the impact of Dutch colonial rule on the economic, political, social, and educational sectors in Jambi City from 1906 to 1942. The research aims to explore the Dutch position during the colonial period and its implications for the people of Jambi, who experienced both benefits and oppression. Employing a historical research method, the study follows four stages: heuristics (data collection), source criticism, interpretation, and historiography. The findings reveal the Dutch role as Resident in Jambi from 1906-1942, highlighting the early period of Dutch presence (1906-1920), the colonial heyday (1920-1929), and the decline of Dutch influence (1929-1942). The research underscores the complex legacy of Dutch colonialism in Jambi, illustrating both advancements and exploitation experienced by the local population. Furthermore, it provides a nuanced understanding of the shifts in power dynamics and their lasting effects on the region's development.